2015
DOI: 10.3389/fneur.2015.00130
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Autonoetic Awareness of Recent Autobiographical Episodes and Accelerated Long-Term Forgetting in a Patient with Previously Unrecognized Glutamic Acid Decarboxylase Antibody Related Limbic Encephalitis

Abstract: We describe a 35-year-old male patient presenting with depressed mood and emotional instability, who complained about severe anterograde and retrograde memory deficits characterized by accelerated long-term forgetting and loss of autonoetic awareness regarding autobiographical memories of the last 3 years. Months before he had experienced two breakdowns of unknown etiology giving rise to the differential diagnosis of epileptic seizures after various practitioners and clinics had suggested different etiologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Both tests, either taken alone or and in combination, are well-suited for monitoring memory in limbic encephalitis [ 11 , 18 , 34 , 45 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both tests, either taken alone or and in combination, are well-suited for monitoring memory in limbic encephalitis [ 11 , 18 , 34 , 45 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…The patient complained about anterograde as well as retrograde episodic memory problems (loss of autonoetic awareness of recent biographical memories and accelerated long-term forgetting). Over several months, the patient searched for a doctor and was diagnosed as suffering from burn-out and depression [85]. Here, the cognitive and behavioral problems preceded the epilepsy.…”
Section: When Seizures As Well As Cognitive and Mood Problems Represementioning
confidence: 99%
“…Studies in patients with focal lesions limited to the CA1 region of the hippocampus attribute a crucial role in autobiographic memory retrieval, mental time travel, and autonoetic consciousness to CA1. 32,33 Most interesting, these cognitive functions have been shown to be impaired in GAD-LE, 34 It is open to discussion why CA1 is selectively affected in GAD-LE. It has been shown that CA1 is particularly vulnerable to a variety of pathologic conditions such as ischemia, inflammation, or increased metabolic demand related to epileptic activity 27,35 and CA1 neurons express an extraordinary high density of N-methyl-D-aspartate NR2 subunits.…”
Section: Autoantibody-specificitymentioning
confidence: 99%